2007
DOI: 10.1021/es070224i
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Photocatalytic Degradation of C.I. Reactive Black 5 at pH 12.0 Using SrTiO3/CeO2 as the Catalyst

Abstract: The photocatalytic degradation mechanism of an azo dye, C.I. Reactive Black 5 (RB5), has been investigated in an aqueous suspension of SrTiO3/CeO2 composite under 250 W UV irradiation at pH 12.0. The process was studied by monitoring the change in RB5 concentration and the intermediate products employing UV-visible spectrophotometry, ion chromatography (IC), and gas chromatography/ mass spectrometry (GC/MS) techniques and depletion in total organic carbon (TOC) content as a function of irradiation time. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(88 citation statements)
references
References 28 publications
1
85
0
2
Order By: Relevance
“…Iodide ion is used as a scavenger that can react quickly with hydroxyl radicals produced at the surface of nZVI particles with a rate constant of 1.2 · 10 10 /(M$s) (Martin et al, 1995;Song et al, 2007). As seen in Fig.…”
Section: Identification Of Reactive Speciesmentioning
confidence: 99%
“…Iodide ion is used as a scavenger that can react quickly with hydroxyl radicals produced at the surface of nZVI particles with a rate constant of 1.2 · 10 10 /(M$s) (Martin et al, 1995;Song et al, 2007). As seen in Fig.…”
Section: Identification Of Reactive Speciesmentioning
confidence: 99%
“…Decoloration of azo dyes was related to the cleavage of nitrogen double bond of azo dyes, as the most reactive site from oxidative attack positive hole, hydroxyl radical and reduced by electron in the conduction band 18) . RB5 contains two azo bonds, therefore rapid decolorization of RB5 indicated that the chromophoric azo bond of dye molecule was destroyed immediately.…”
Section: Resultsmentioning
confidence: 99%
“…Mineralization of organic dye substances into CO 2 and H 2 O required a longer time, due to the formation of reaction intermediates in the solution during the degradation of the dye. Generally, the degradation of dye is represented by the typical wavelength of naphthalene and condensed ring aromatics at wavelength of around 300 nm and the benzene group at about 254 nm 18) . The intermediates of some organic dye compounds can exist for a long time in nature and are toxic to aquatic life 20) ; thus complete destruction of dye intermediates is important.…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 powders could be employed in solar and UV irradiation systems (photoreactors) because this semiconductor has a high transparency to visible light, high refractive index, and low absorption coefficient. Wide range of metal oxides and sulfides have been used as photocatalysts including ZnO (Daneshvar et al, 2004;Sakthivel et al, 2003;Kormann et al, 1988;Khodj et al, 2001;Gouvêa et al, 2000;Lizama et al, 2002;Kansal et al, 2007;Chakrabarti and Dutta, 2004), WO 3 (Waldner et al, 2007;Sayama et al, 2010;Saepurahmanet et al, 2010;Cao et al, 2011), WS 2 (Jing and Guo, 2007), Fe 2 O 3 (Chen et al, 2001;Bandara et al, 2001;Pal and Sharon, 1998), V 2 O 5 (Akbarzadeh et al, 2010;Teramura et al, 2004a,b), CeO 2 (Lin and Yu, 1998;Coronado et al, 2002;Ji et al, 2009;Song et al, 2007), CdS (Bessekhouad et al, 2004;Reuterġardh and Langphasuk, 1997;Tang and Huang, 1995), ZnS (Torres-Martínez et al, 2001), and CuO (Lim and Kim, 2004;Sathishkumar et al, 2011;Nezamzadeh-Ejheieg and Hushmandrad, 2010). The light intensity in homogeneous and heterogeneous photoreactors determines the LVREA which is proportional to the rate of photochemical reaction.…”
Section: Principles Of Photocatalysismentioning
confidence: 99%